(untitled) (Kairaranga, 2023)
The foundation of inclusive education is that every learner has the potential to contribute positively to society. A sense of belonging to society is vital to this contribution, and to the growth and development of children and young people with autism. New Zealand has made some positive progress towards inclusive education, with some education institutes understanding that all children have the right to be educated and to receive the best possible education they can, regardless of ethnicity, culture or disability. However, research indicates that there are still barriers to inclusive education, and these barriers have drastic lifelong implications for children and young people with autism. This paper outlines what inclusive education is, identifies barriers from the perspectives of research, educators and families, and discusses lifelong implications of a non-inclusive education on autistic children and young people.